EFEKTIVITAS BIMBINGAN KELOMPOK UNTUK MENINGKATKAN LITERASI SISWA DI SEKOLAH SANGGAR BIMBINGAN KAMPUNG BARU MALAYSIA - Annisa; Hasibuan, M. Fauzi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of group guidance in improving students' literacy. This research employs a quantitative approach with a pre-test and post-test design, utilizing the IBM SPSS program for data analysis. The study was conducted at Sanggar Bimbingan Kampung Beru School, Malaysia. The results indicate that group guidance services have been proven effective in enhancing students' literacy, with an N-Gain score of 0.41, falling within the range of 0.3 ≤ N-Gain ≤ 0.7, and an Asymp. Sig (2-tailed) probability value of 0.001 < 0.05. This effectiveness is evident from the comparison between students' pre-test scores before receiving group guidance services and their post-test scores after receiving the intervention